Rainfall infiltration and soil hydrological characteristics below ancient forest, planted forest and grassland in a temperate northern climate. Issue 4 (6th August 2015) - Archer, Nicole A. L.; Otten, Wilfred; Schmidt, Sonja; Bengough, A. Glyn; Shah, Nadeem; Bonell, Mike
Abstract: How rainfall infiltration rate and soil hydrological characteristics develop over time under forests of different ages in temperate regions is poorly understood. In this study, infiltration rate and soil hydrological characteristics were investigated under forests of different ages and under grassland. Soil hydraulic characteristics were measured at different scales under a 250‐year‐old grazed grassland (GL), 6‐year‐old (6yr) and 48‐year‐old (48yr) Scots pine ( Pinus sylvestris ) plantations, remnant 300‐year‐old individual Scots pine (OT) and a 4000‐year‐old Caledonian Forest (AF). In situ field‐saturated hydraulic conductivity ( Kfs ) was measured, and visible root:soil area was estimated from soil pits. Macroporosity, pore structure and macropore connectivity were estimated from X‐ray tomography of soil cores, and from water‐release characteristics. At all scales, the median values for Kfs, root fraction, macroporosity and connectivity values tended to AF > OT > 48yr > GL > 6yr, indicating that infiltration rates and water storage increased with forest age. The remnant Caledonian Forest had a huge range of Kfs (12 to >4922 mm h −1 ), with maximum Kfs values 7 to 15 times larger than those of 48‐year‐old Scots pine plantation, suggesting that undisturbed old forests, with high rainfall and minimal evapotranspiration in winter, may act as important areas for water storage and sinks for storm rainfall to infiltrate and transport to deeper soil layers via preferential flow. The importance of the development of soil hydrological characteristics under different aged forests is discussed. Copyright 2015 British Geological Survey. Ecohydrology © 2015 John Wiley & Sons, Ltd.